Mitochondrial Dysfunction and Therapeutic Targets in Auditory Neuropathy - Baoyi Feng; Chenxi Jin; Zhenzhe Cheng; Xingle Zhao; Zhuoer Sun; Xiaofei Zheng; Xiang Li; Tingting Dong; Yong Tao; Hao Wu (Neural Plasticity)
Sensorineural hearing loss (SNHL) becomes an inevitable worldwide public health issue, and deafness treatment is urgently imperative; yet their current curative therapy is limited. Auditory neuropathies (AN) were proved to play a substantial role in SNHL recently, and spiral ganglion neuron (SGN) dysfunction is a dominant pathogenesis of AN. Auditory pathway is a high energy consumption system, and SGNs required sufficient mitochondria. Mitochondria are known treatment target of SNHL, but mitochondrion mechanism and pathology in SGNs are not valued. Mitochondrial dysfunction and pharmacological therapy were studied in neurodegeneration, providing new insights in mitochondrion-targeted treatment of AN. In this review, we summarized mitochondrial biological functions related to SGNs and discussed interaction between mitochondrial dysfunction and AN, as well as existing mitochondrion treatment for SNHL. Pharmaceutical exploration to protect mitochondrion dysfunction is a feasible and effective therapeutics for AN.